Il regionalismo commerciale dopo l'Uruguay Round (Commercial regionalism after the Uruguay Round) - E. GRILLI (Moneta e Credito, 2013)
The attempts by a number of countries to partially or totally liberalise their trade on a discriminatory basis have long been documented. Despite the wide spread of the GATT in both geographical and temporal terms, regionalism has never easily co-existed with commercial multilateralism. The Uruguay Round has taken place in a period in which several key countries have radically changed trade policies. In this light, the search for a new balance between the multilateralism de jure and the regionalism de facto practiced by many members of the GATT took on importance as a test of their intentions to continue or not with the existing multilateral order or rather to modify it in a regional sense. This paper reviews the problems of coexistence between regionalism and multilateralism in the international trade order and demonstrates how few concrete conclusions can be drawn from an examination of both the theory and the empirical evidence.